Noninvasive Prenatal Testing - When Is It Advantageous to Apply - Liehr, Thomas (Biomed Hub, 2017)
Nowadays it is common sense in obstetrics that an increased risk for pregnancy loss due to invasive testing does not exist. Nonetheless, noninvasive prenatal testing (NIPT) is a hot topic, even though this approach does not provide a reduction of unintentionally induced abortions. NIPT has a number of shortcuts which are highlighted in this review, including: (1) in NIPT placental rather than fetal DNA is studied, (2) NIPT fails in 2–6% of cases, and (3) trisomy 21 accounts for only ∼50% of existing chromosomal aberrations. Thus, we agree with the literature that NIPT is a fascinating possibility to gain information on unborn life from minimal amounts of DNA. However, it remains a pure risk estimation test directed towards the detection of specific chromosomal abnormalities from peripheral blood of the pregnant woman. It is important to highlight that families buying this test, and getting a normal result, may be provided with a false sense of security. Thus, careful and comprehensive genetic counselling should be performed before the test is offered, and should include a clear explanation of the advantages and disadvantages, as well as limitations, compared to other methods.